Resenha: Unconstitutional Constitutional Amendments: The Limits of Amendment Power (Oxford University Press, 2017), de Yaniv Roznai - Benvindo, Juliano Zaiden (Revista de Investigações Constitucionais, 2018)
Resenha do livro "Unconstitutional Constitutional Amendment: The Limits of Amendment Power, de Yaniv Roznai (Oxford Univeristy Press, 2017).